Providing a Model for the Labor Relations System in Knowledge-Based Organizations (Engineering Companies Affiliated with the Ministry of Defense and Armed Forces Support) - Ataei Nasab, Shokrollah; Valikhani, Mashaallah; Hosseini Golafshani, Seyed Ahmad (Management Strategies and Engineering Sciences, 2024)
The main objective of this article is to propose a model for the labor relations system in knowledge-based organizations (engineering companies affiliated with the Ministry of Defense and Armed Forces Support). The research method is mixed (qualitative-quantitative). In the qualitative section, grounded theory was employed using MAXQDA14 software to identify indicators related to the labor relations system in knowledge-based organizations. The research population included experts in management specializing in public administration, human resources, and organizational relations (who had authored books or articles) as well as managers and deputies of engineering companies affiliated with the Ministry of Defense and Armed Forces Support. Based on the theoretical saturation criterion, 15 participants were purposefully selected. In the quantitative section, a developmental-applied method was used. The quantitative statistical population consisted of all employees of engineering companies affiliated with the Ministry of Defense and Armed Forces Support, and the sample size was determined using Cochran's formula. Accordingly, 384 participants were randomly selected as the sample. As a result, 131 initial concepts (open codes), 19 main concepts (axial codes), and 6 selective codes were identified. Quantitative results indicated that the influence of contextual factors on strategic factors, with a coefficient of 0.896, represents the strongest relationship, while the relationship between the main phenomenon and strategies, with a coefficient of 0.443, is the weakest. The proposed model, comprising four dimensions (understanding, adaptation, generalization, and control), was validated by expert opinion.